1969
DOI: 10.1017/s0022172400041541
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic activity of the alpha and theta toxins ofClostridium welchii

Abstract: SUMMARYThe lecithinase and haemolytic activity of thirty strains ofCl. welchiiisolated from food, faeces, and soil, was studied. The strains from foods produced smaller amounts of lecithinase and were, in general, less haemolytic than the strains isolated from soil and faeces.The haemolytic activity ofCl. welchiion erythrocytes from different animal species displayed considerable variation. Sheep erythrocytes were the most sensitive to the action of alpha toxin, whereas rabbit blood was most sensitive to haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1970
1970
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Canada & Strong (18) reported that C. perfringens appeared in the livers and feces of germ free mice force-fed with this organism. Schulze, Nakamura & J utila (164) observed an interesting phenomenon. Germ-free mice that were force-fed C.…”
Section: Experimental Models In Animalsmentioning
confidence: 88%
See 2 more Smart Citations
“…Canada & Strong (18) reported that C. perfringens appeared in the livers and feces of germ free mice force-fed with this organism. Schulze, Nakamura & J utila (164) observed an interesting phenomenon. Germ-free mice that were force-fed C.…”
Section: Experimental Models In Animalsmentioning
confidence: 88%
“…The measurement of enzymatic degradation products of lecithin is highly quantitative ( (15) assayed the toxin by determining the amount of hemoglobin released from hemolyzed erythrocytes. This is an easily measurable event (79,161,163) but it is less quantifiable than some of the other methods.…”
Section: Alpha Toxinmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxin has been found to split other phospholipids (sphingomyelin and lysophosphatidylcholine) as well (21,23). The toxin is known to be hemolytic (19,24,44), dermonecrotic (49), and lethal (49). The hemolytic activity of alpha-toxin is observed by incubating the toxin with sheep erythrocytes at 37°C and then chilling the preparation to below 10°C (the phenomenon of hot-cold hemolysis) (47).…”
mentioning
confidence: 99%